Capital-skill complementarity: evidence from manufacturing industries in Ghana - Gokhan H. Akay; Mutlu Yuksel (Institute for the Study of Labor (IZA), 2009)
Using U.S. manufacturing data, Griliches (1969) found evidence suggesting that capital equipment was more substitutable for unskilled than skilled labor. Griliches formulated this finding as the capital-skill complementarity hypothesis. The purpose of this study is to determine whether the capital-skill complementarity framework holds for Ghana manufacturing plants in industry and aggregate level. We use an unbalanced panel of plant-level data for manufacturing firms in Ghana during the 1991 and 1997 in four industries (food-bakery, textiles-garments, wood-furniture and metal-machinery). Our findings suggest that capital-skill complementarity holds in aggregate level and wood-furniture sector in Ghana. However, we reject the capital-skill complementarity hypothesis for food-bakery, textile-garment and metal-machinery sectors.
Keywords: J30; O55; 330; Capital-skill complementarity; elasticity of substitution; translog cost function; Kapital; Qualifikation; Komplementärgut; Faktorsubstitution; Substitutionselastizität; Mittelständische Industrie; Kostenfunktion; Ghana